2004
DOI: 10.1063/1.1686902
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of boron carbide

Abstract: Boron carbide displays a rich response to dynamic compression that is not well understood. To address poorly understood aspects of behavior, including dynamic strength and the possibility of phase transformations, a series of plate impact experiments was performed that also included reshock and release configurations. Hugoniot data were obtained from the elastic limit (15–18 GPa) to 70 GPa and were found to agree reasonably well with the somewhat limited data in the literature. Using the Hugoniot data, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(153 citation statements)
references
References 21 publications
9
138
2
4
Order By: Relevance
“…Therefore, B 4 C has been an important structural ceramic for the applications where both high strength and lightweight are required 6,7 . However, unlike other high performance ceramics, B 4 C displays an anomalous reduction in shear strength under pressures [8][9][10][11] . High-resolution electron microscopy of shock-loaded fragments revealed that the formation of nano-scale amorphous shear bands is responsible for the dramatic loss of shear strength at high pressures 12 .…”
mentioning
confidence: 99%
“…Therefore, B 4 C has been an important structural ceramic for the applications where both high strength and lightweight are required 6,7 . However, unlike other high performance ceramics, B 4 C displays an anomalous reduction in shear strength under pressures [8][9][10][11] . High-resolution electron microscopy of shock-loaded fragments revealed that the formation of nano-scale amorphous shear bands is responsible for the dramatic loss of shear strength at high pressures 12 .…”
mentioning
confidence: 99%
“…Such information should provide increased understanding of experimentallyobtained results from plate impact tests [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The theory is implemented in a dynamic Lagrangian finite element (FE) code [5], and 2D FE meshes are constructed of the initial microstructures of a KE rod sectioned either transversely or parallel to the rod axis (i.e., the extrusion direction). Simulations of high rate impact, wave propagation, and spall are conducted, reminiscent of conditions present in plate impact experiments [6,7]. We show how statistical data acquired from simulations depict effects of the microstructure and model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…After that it drops and shear strength could be obtained by the value of shear component. The calculated values are compared with the data, obtained from the release and reshock experiments [18]. These data correspond to the damaged state of the boron carbide, which is realized after the propagation of the first shock wave.…”
Section: Simulations Of Boron Carbidementioning
confidence: 99%